Governance Quality In Emerging Economies And Its Implications For Green Finance: Empirical Evidence From Panel Linear And Nonlinear Analysis - Epor, Simon Okaja (Journal of Ecohumanism, 2025)
Our study identified that poor governance quality in emerging economies, being detrimental concern to financial development, could also explain the poor depth and growth of the green finance market. This prompted the study to consider the influences of institutional quality and governance quality in explaining green finance development in twenty-one (21) emerging economies from 2010 to 2022. Due to data availability factor and nature of data, the most suitable technique is the linear and nonlinear panel ARDL/PMG and estimators to address the dynamic implications of governance on green finance market in emerging economies. The findings showed that green finance was improved when corruption control, government effectiveness and governance index in emerging economies are considered independently but impeded by political stability. However, when considered collectively, only government effectiveness was beneficial to green finance, even though insignificantly, while both political stability and corruption control exert significant negative effect on green finance. Dynamically the index of governance exerts proportional influences on green finance in emerging economics, with the positive shock supporting green finance as against the negative shock that impeded it. The findings offer options for integrated environmental policies into institutional reforms because of their significant influence on green finance development.